Thrips in Florida Strawberry Crops - Jeffrey D. Cluever; Hugh A. Smith; Joe E. Funderburk; Galen Frantz (EDIS, 2015)
Strawberries grown in Florida are attacked by several pests, including flower thrips. Western flower thrips and common blossom thrips (both invasive) can cause damage to strawberries in Florida; but, while the native Florida flower thrips is commonly found in strawberry blossoms, it hasn’t been established that it can cause economic damage to strawberry. This 9-page fact sheet describes thrips damage, characteristics to distinguish among the three species, and methods of control. Written by Jeff D. Cluever, Hugh A. Smith, Joe E. Funderburk, and Galen Frantz, and published by the UF Department of Entomology and Nematology, January 2015. (Photo: H. A. Smith)